2020
DOI: 10.1111/php.13207
|View full text |Cite
|
Sign up to set email alerts
|

Irradiance, Photofrin® Dose and Initial Tumor Volume are Key Predictors of Response to Interstitial Photodynamic Therapy of Locally Advanced Cancers in Translational Models

Abstract: The objective of the present study was to develop a predictive model for Photofrin®‐mediated interstitial photodynamic therapy (I‐PDT) of locally advanced tumors. Our finite element method was used to simulate 630‐nm intratumoral irradiance and fluence for C3H mice and New Zealand White rabbits bearing large squamous cell carcinomas. Animals were treated with light only or I‐PDT using the same light settings. I‐PDT was administered with Photofrin® at 5.0 or 6.6 mg kg−1, 24 h drug‐light interval. The simulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Heat can be effective and is challenging to use ( 34 , 35 ). Light is being used in PDT to treat not only shallow lesions but also at depth via catheter methodologies with planning systems and new agents that respond at greater depths ( 36 , 37 ). Both electrical and magnetic fields show promise in treating tumors with and without the use of nanoparticles ( 38 , 39 ).…”
Section: Physicsmentioning
confidence: 99%
“…Heat can be effective and is challenging to use ( 34 , 35 ). Light is being used in PDT to treat not only shallow lesions but also at depth via catheter methodologies with planning systems and new agents that respond at greater depths ( 36 , 37 ). Both electrical and magnetic fields show promise in treating tumors with and without the use of nanoparticles ( 38 , 39 ).…”
Section: Physicsmentioning
confidence: 99%
“…FullMonteWeb 31 stands out as a comprehensive Cloud-based treatment planning platform to model light dose distribution for interstitial PDT and to optimize treatment parameters, including fiber positions and power allocation 36 with a choice of CUDA 27 or FPGA 43 acceleration. Besides conventional light dose, other dose metrics are gaining a scientific ground -irradiance threshold, 44,45 PDT-dose 46,47 , and singlet oxygen dose 39,46 -to potentially become the principal predictors of responses to PDT treatments of solid tumors. Designing and implementing an MC light transport with a moving light source will be the first step in providing a treatment planning platform for icav-PDT to treat plural lung cancer or potentially any other tumor located in proximity to a tissue surface that forms a cavity.…”
Section: Introductionmentioning
confidence: 99%
“…In our recent preclinical studies, we used an image-based finite element method (FEM) to guide I-PDT light delivery, which demonstrated that in addition to PS tumor retention, the baseline tumor volume, and fluence, the intratumoral irradiance is a key parameter indicative of tumor response to I-PDT with porfimer sodium (Photofrin ® , Pinnacle Biologics Inc., Bannockburn, IL, USA) [10,16]. In external beam PDT of superficial tumors, low irradiance at the tumor surface is the key parameter for effective response PDT [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In external beam PDT of superficial tumors, low irradiance at the tumor surface is the key parameter for effective response PDT [17,18]. For I-PDT of locally advanced cancers in mice and rabbits, we reported that exceeding the minimal irradiance at the tumor margins is the key parameter for effective response with intravenous injection of 5 mg/kg Photofrin at 24 ± 2 h prior to laser light [10,16]. Thus, we showed that irradiance of 5.0 mW/cm 2 with a fluence of 45 J/cm 2 at the margins will result in a significantly lower cure rate (p < 0.05) when compared to 8.6 mW/cm 2 with 45 J/cm 2 [10,16], which we define in this work as the effective rate-based light dose in Photofrin ® -mediated I-PDT with 630 nm laser light.…”
Section: Introductionmentioning
confidence: 99%